Memperkuat Ekonomi melalui Kewarganegaraan: Peran Warga Negara dalam Mendorong Keberlanjutan Ekonomi - Sarah Angelina Panggabean; Della Ayu Wulandari; Agus Tina Wulandari; Furqon Mubarok; Herli Antoni (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to explore the role of citizens in encouraging economic sustainability through active participation in various sectors. Using the literature study method, this study analyzes data related to the contribution of citizens to the Indonesian economy. Key findings show citizen participation in responsible consumption, social entrepreneurship, tax awareness, and policy advocacy has an impact on the country’s economy. Consumption of local products accounts for 57% of Indonesia’s GDP, with the trend of purchasing MSME products increasing by 25% during the pandemic. In addition, social entrepreneurship initiatives such as "Zero Waste Indonesia" play a role in creating jobs and supporting the circular economy. However, challenges such as low financial literacy at 38%, cumbersome bureaucracy, and distrust of institutions hinder citizen participation. Supporting factors such as civic education encouraging cooperation, digital technology penetration which reached 77%, and government policies that support local products contribute to strengthening the role of citizens. Despite the challenges, active citizen participation in the economy can accelerate economic sustainability through more conscious consumption, innovation in social entrepreneurship, and supportive policies.